1991
DOI: 10.1007/bf02011485
|View full text |Cite
|
Sign up to set email alerts
|

Colonic diverticulitis in young patients with chronic renal failure and transplantation

Abstract: The association of colonic diverticulitis with chronic renal failure is well known. In those patients with "adult" autosomal dominant polycystic kidney disease, colonic diverticulitis is an especially common complication. We present two young patients (one teenager and one mid-twenties) who developed intra-abdominal abscess several years after renal transplantation. Neither patient had autosomal dominant polycystic disease nor a known history of gastrointestinal problems but both proved to have underlying, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Wada et al reported that CKD was a risk factor for rebleeding in CBD (OR 2.3) [30]. Studies have also reported that diverticulosis develops at a young age in some patients with renal failure [31,32]. In patients with renal failure, the presence of uremic platelet dysfunction is considered as a cause of gastrointestinal bleeding [33].…”
Section: Discussionmentioning
confidence: 99%
“…Wada et al reported that CKD was a risk factor for rebleeding in CBD (OR 2.3) [30]. Studies have also reported that diverticulosis develops at a young age in some patients with renal failure [31,32]. In patients with renal failure, the presence of uremic platelet dysfunction is considered as a cause of gastrointestinal bleeding [33].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence is proportional to age with a prevalence of less than 5% at age 40 and 60–65% at the age of 80 years [28]. However, in dialysis patients with kidney disease from any cause, diverticulosis may occur at younger age and may be more severe [30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…Most features of diverticular disease, including presentation, and management, are similar in those with and without renal failure. However, compared to those without renal impairment, the disease may occur at a younger age (less than 40 years) and may be more severe in patients with renal dysfunction [ 12 ]. Complications, such as perforation, are associated with a higher mortality rate, and patients may have a higher rate of bleeding resulting from iatrogenic anticoagulation and/or platelet dysfunction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%